CHINESE EUPHEMISM ACQUISITION BY L2 LEARNERS IN INDONESIA - Guan, Nan; Silalahi, Ronald Maraden Parlindungan (Bambuti, 2023)
As one of the most widely used communication strategies, euphemism is an important language behaviour in human society. Chinese euphemism has its unique characteristics reflecting the Chinese nation’s moderate and harmonious cultural psychology. This feature is particularly prominent in the daily communication applications of Chinese, so that it is often difficult for L2 learners to understand it. This article focuses on the acquisition of Chinese euphemism as the research object, and takes the inter-language pragmatics as the theoretical background, using the questionnaire as the main research method combining with the interview method to investigate the Chinese euphemism acquisition by the intermediate and advanced level students from the Chinese Department in a Jakarta private university. The results show that, in general, students have the awareness of using Chinese euphemism. The language level has positive correlation with euphemism acquisition. The error frequency in conventional euphemism is supreme to that in non-conventional euphemism. The euphemism used by the students has obvious inter-language characteristics in structure and speech strategies. Negative pragmatic transfer constraints students in euphemism acquisition. Insufficient language ability and cultural differences are the crucial obstacles. Some relevant suggestions from the perspectives of teacher-student interaction and textbook design are proposed to improve the euphemism acquisition for L2 learners.